2017
DOI: 10.1007/s40495-016-0078-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drug Treatment at Neonatal Ages on Variability of Drug Metabolism and Drug-Drug Interactions in Adult Life

Abstract: Purpose of review As the number of patients taking more than one medication concurrently continues to increase, predicting and preventing drug-drug interactions (DDIs) is now more important than ever. Administration of one drug can cause changes in the expression and activity of drug metabolizing enzymes (DMEs) and alter the efficacy or toxicity of other medications that are substrates for these enzymes, resulting in a DDI. In today’s medical practice, potential DDIs are evaluated based on the current medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Whether the capacity for enzymatic induction varies at different ages during postnatal liver maturation is also not understood. Several studies have additionally suggested neonatal exposures to inducer drugs, particularly the antiepileptic drug (AED) phenobarbital, can cause permanent alterations to expression and activities of P450s in adult rodents Shapiro, 1996, 2005;Tien et al, 2015Tien et al, , 2017Piekos et al, 2017). There also appears to be a window of sensitivity during neonatal life that allows the imprinting of lasting changes to P450 expression following treatment (Tien et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the capacity for enzymatic induction varies at different ages during postnatal liver maturation is also not understood. Several studies have additionally suggested neonatal exposures to inducer drugs, particularly the antiepileptic drug (AED) phenobarbital, can cause permanent alterations to expression and activities of P450s in adult rodents Shapiro, 1996, 2005;Tien et al, 2015Tien et al, , 2017Piekos et al, 2017). There also appears to be a window of sensitivity during neonatal life that allows the imprinting of lasting changes to P450 expression following treatment (Tien et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism. The latest literature suggests that persistent epigenetic changes in the promoters of CAR target genes, including Cyp2b10, are responsible for prolonged induction within the F0 generation in the liver (Chen et al, 2012;Peng and Zhong, 2015;Tien et al, 2015Tien et al, , 2017Li et al, 2016;Piekos et al, 2017;Lodato et al, 2018). Our work indicates that at least some of these effects may have been driven by activator accumulation rather than by stable DNA modifications.…”
Section: Soft Inheritance Of Hepatic Inductionmentioning
confidence: 61%
“…Mechanisms regulating paediatric gene expression and induction may also differ from those of adults. Drug metabolism occurs through phase I and phase II reactions, which, in newborns and children, are not entirely developed processes 35…”
Section: Drug Metabolismmentioning
confidence: 99%